What we do not know about advergames: a literature review - Cañete Sanz, Laura; De La Hera, Teresa (Frontiers in Communication, 2023)
This paper presents the findings of a systematic literature review on the academic study of advergames. The evolution of the marketing paradigm has recently opened new avenues for the study of advergames (see Vashist, Royne, & Sreejesh, 2019), such as understanding how the brand narrative could be used within a game to achieve diverse marketing objectives (e.g. Villén Higueras, 2017), their value for brand engagement through games (e.g. Martí Parreño, Ruiz Mafé & Scribner, 2015), or new applications of the specific characteristics of emerging platforms for advergaming (e.g. Pérez, Froufe & Costa, 2013). This paper, therefore, aims to provide an overview of the state of the art on the academic study of advergames to identify necessary expansions of academic attention to advergames in order to encompass the full capabilities of branded entertainment, and advergame design. We conducted a systematic literature review of 122 papers on the topic of advergames published between 2005 and 2021 indexed at the Web of Science Core Collection. The data extraction and analysis followed the six-step thematic analysis approach by Braun and Clarke (2006). The results show that the main research domains explored within the academic studies of advergames were related to (1) the study of the advergame effects on the impact on health through the promotion of food products for children; (2) and the effects of advergames on the purchase intention. The themes related to (3) brand narratives and innovative forms; or (4) the effects on brand loyalty were underrepresented. The results of this study conclude identifying specific gaps in the literature and a necessity to take a more flexible approach in the analysis of advergames that takes into consideration the evolution of the marketing ecosystem and provides theoretical insights that can open new avenues for the study of the effectiveness of advergames from a different perspective.